Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Effects of Spartina alterniflora Invasion and Mangrove Restoration on Soil Microbial Functional Diversity - Yongni He; Genmei Lin; Xinyi Gao; Yiting Cao; Naxu Hu; Rui Li; Jianxiang Feng (Journal of Soil Science and Plant Nutrition, 2022)

Baicalin-berberine complex nanocrystals orally promote the co-absorption of two components - Ziwei Li; Yiting Liu; Jilin Wang; Xiaojiao Feng; Ebuka-Olisaemeka Nwafor; Ying Zhang; Rui Liu; Wenli Dang; Qingqing Zhang; Changxiang Yu; Jiaxin Pi; Zhidong Liu (Drug Delivery and Translational Research, 2022)

Effects of STAT3 Inhibitor BP-1-102 on The Proliferation, Invasiveness, Apoptosis and Neurosphere Formation of Glioma Cells in Vitro - Cheng-Chen Zhang; Ting Wu; Li Guan; Yu-Jue Wang; Rui-Qin Yao; Dian-Shuai Gao; Feng Li (Cell Biochemistry and Biophysics, 2022)

An improved bicubic imaging fitting algorithm for 3D radar detection target - Fan-Ruo Li; Feng Yang; Rui Yan; Qiao Xu; Yi-Jin Li; Hong-Jia Xing (Applied Geophysics, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Three new compounds from the leaves of Castanopsis tibetana Hance - Ya-Feng Wang; Rui-Jie He; Dian-Peng Li; Yong-Lin Huang (Natural Product Research, 2022)

Triphenylpyrazoline ketone chlorophenols as potential candidate compounds against Parkinson’s disease: design, synthesis, and biological evaluation - Ning Ning Cheng; Le Hua Zhang; Rui Ge; Xiu E. Feng; Qing Shan Li (Medicinal Chemistry Research, 2022)

Orbit determination, clock estimation and performance evaluation of BDS-3 PPP-B2b service - Chengpan Tang; Xiaogong Hu; Jinping Chen; Li Liu; Shanshi Zhou; Rui Guo; Xiaojie Li; Feng He; Jinhuo Liu; Jianhua Yang (Journal of Geodesy, 2022)

Association between ambient air pollution exposure during pregnancy and gestational diabetes mellitus: a meta-analysis of cohort studies - Xinyu Zhou; Changlian Li; Han Cheng; Junyi Xie; Feng Li; Lishan Wang; Rui Ding (Environmental Science and Pollution Research, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Spatial-temporal distribution and tectonic setting of Mesozoic W-mineralized granitoids in the Xing-Meng Orogenic Belt, NE China - Wei Xie; Qing-Dong Zeng; Rui-Liang Wang; Jin-Jian Wu; Zhe-Ming Zhang; Feng-Chun Li; Zhuang Zhang (International Geology Review, 2022)

Temporal Dynamics in Energy Fluxes and Trophic Structure of a Portunus trituberculatus Polyculture Ecosystem During Different Culture Periods - Jie Feng; Xiang-Li Tian; Shuang-Lin Dong; Rui-Peng He; Kai Zhang; Dong-Xu Zhang; Qing-Qi Zhang (Frontiers in Marine Science, 2022)
Swimming crab ( Portunus trituberculatus ) are an important aquaculture species in eastern coastal areas of China. To improve the understanding of P. trituberculatus culture ecosystem functioning, the dynamics of energy flow and trophic structure of a P. trituberculatus polyculture system (co-culture with white shrimp Litopenaeus vannamei and short-necked clam Ruditapes philippinarum ) were investigated in this study. Three Ecopath models representing the early, middle, and late culture periods of a P. trituberculatus polyculture ecosystem, respectively, were constructed to compare ecosystem traits at different culture periods. The results demonstrated that detritus was the main energy source in this polyculture ecosystem, and most of the total system throughput occurred at trophic levels I and II. Artificial food input and consumption by the culture organisms increased from early to middle and late periods, which produced marked impacts on biomass structure and primary production. R. philippinarum was considered to have a dominant influence on phytoplankton community dynamics which changed from nano- to pico-phytoplankton predominance, from the middle to the late period. Considering the low utilization efficiency of pico-phytoplankton production, large amounts of detritus accumulated in the sediment in the late period, which may constitute a potential risk for the ecosystem. Ecological network analyses indicated that the total energy flow and level of system organization increased from the early to the middle and late periods, whereas food web complexity and system resilience decreased from early to middle and late periods, which may indicate a trend of decreasing ecosystem stability. The system may be further optimized by increased stocking density of R. philippinarum and by introducing macro-algae at a suitable biomass to increase ecosystem stability, energy utilization efficiency, and aquaculture production.

Otolith Marking With Strontium for Stock Assessment in Coilia nasus - Ming-Zhi Liu; Ri-jin Jiang; Hui Zhang; Fan Yang; Xia-Fang Li; Guang-Peng Feng; Rui Yin; Feng Chen (Frontiers in Marine Science, 2022)
Mass stock enhancement and release are excellent ways to recover Coilia nasus resources. However, it is challenging to evaluate stock enhancement effectively, and it is important to establish a method suitable for estimating C. nasus populations. We explored the effectiveness of marking otoliths in these fish with strontium by immersing C. nasus in hexahydrate strontium chloride solutions. We used laser ablation inductively coupled plasma mass spectrometry to measure the strontium content of otoliths and fish bodies. The larvae (40 d post hatch) were reared in five different concentrations of strontium (0, 12, 24, 48, and 60 mg/L) for 7 d, followed by treatment in non-additive water for 3 wk. The results showed that the cumulative mortality rate was not significantly different between treatment and control groups ( P >0.05), except in the group treated with 24 mg/L strontium. The swimming and feeding behaviors did not change significantly, indicating that strontium did not negatively affect survival in this species. The strontium/calcium ratios of otoliths in the control group were stable (1.78–2.32 mmol/mol), whereas those of the experimental (marked) groups ranged widely (4.47–61.02 mmol/mol). The strontium/calcium ratios increased with increasing strontium concentration, but gradually returned to baseline values, resulting in a 100% success rate of marking with strontium. Following immersion in 12 mg/L strontium, strontium levels in the body returned to normal after 24 d. In summary, a treatment of 12 mg/L strontium for 4 d was identified as viable for marking. We confirmed the feasibility of strontium marking for the mass marking and release of C. nasus . This marking method does not affect the physiology of the fish and may provide a new approach for reasonable and scientific stock assessment of C. nasus post hatch.

Aberrant Gene Expression of Selenoproteins in Chicken Spleen Lymphocytes Induced by Mercuric Chloride - Jia-Hong Chu; Yu-Xue Yan; Xue-Wei Chen; Pei-Chao Gao; Lan-Xin Li; Rui-Feng Fan (Biological Trace Element Research, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Failure mechanisms and risk mitigation of check dams on the Chinese Loess Plateau: A case study at the Gutun Gully - Rui-jun Jiang; Mao-sheng Zhang; Li Feng; Ping-ping Sun (Journal of Mountain Science, 2022)

Focal white matter microstructural alteration after anthracycline-based systemic treatment in long-term breast cancer survivors: a structural magnetic resonance imaging study - Huawen Zhang; Peng Li; Tonghui Liu; Xueyuan Wang; Wei Feng; Rui Chen; Hengyang Wei; Guoqiang Li; Long Ning; Ming Zhang; Yuchen Zhang (Brain Imaging and Behavior, 2022)

Petrogenesis and tectonic setting of the early-middle triassic subduction-related granite in the eastern segment of East Kunlun: evidences from petrology, geochemistry, and zircon U-Pb-Hf isotopes - Zuo-Chen Li; Xian-Zhi Pei; Paul D. Bons; Rui-Bao Li; Lei Pei; Guo-Chao Chen; You-Xin Chen; Cheng-Jun Liu; Meng Wang; Shao-Wei Zhao; Xiao-Bing Li; Feng Gao (International Geology Review, 2022)

The Antioxidant Role of Selenium via GPx1 and GPx4 in LPS-Induced Oxidative Stress in Bovine Endometrial Cells - Samson O. Adeniran; Peng Zheng; Rui Feng; Elikanah O. Adegoke; Fushuo Huang; Mingjun Ma; Ziming Wang; Olamigoke O. Ifarajimi; Xiaoyu Li; Guixue Zhang (Biological Trace Element Research, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Long-term observations of the chemical composition, fluxes and sources of atmospheric wet deposition at an urban site in Xi’an, Northwest China - Rui-feng Li; Xi-ying Dong; Cong Xie; Liang-ju Zhao (Environmental Monitoring and Assessment, 2022)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Existing form and distribution of fluorine and phosphorus in phosphate rock acid-insoluble residue - Rui Li; Weilong He; Jiangfei Duan; Shengxia Feng; Ziyu Zhu; Yu Zhang (Environmental Science and Pollution Research, 2022)

Variations in bacterial and archaeal community structure and diversity along the soil profiles of a peatland in Southwest China - Wei Li; Mingmo Luo; Rui Shi; Defeng Feng; Zhenan Yang; Huai Chen; Bin Hu (Environmental Science and Pollution Research, 2022)